2022
DOI: 10.24093/awej/vol13no4.28
|View full text |Cite
|
Sign up to set email alerts
|

Identifying English Language Pragmatic Deficits among Children with Autism: Lessons from Fatima’s Home

Abstract: This article addresses a unique language-learning journey of a special child, ‘Fatima’ who is diagnosed with mild autism or Level One Autism Spectrum Disorder. Taking a qualitative perspective, research based on a series of observations and interviews was conducted on Fatima and her caregivers, namely her mother and her two elder siblings. Fatima was primarily diagnosed as having a learning delay, Attention Deficit Hyperactivity Disorder (ADHD) and hyperactivity but not speech development. This study aims to l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Dealing with children who have special needs, including those who have Autism Spectrum Disorder, the problems of language acquisition such as students' pragmatic ability seem to be a greater challenge in some countries [1][2][3][4][5][6]. Autism Spectrum Disorder students face particular learning difficulties, such as pragmatic deficit.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dealing with children who have special needs, including those who have Autism Spectrum Disorder, the problems of language acquisition such as students' pragmatic ability seem to be a greater challenge in some countries [1][2][3][4][5][6]. Autism Spectrum Disorder students face particular learning difficulties, such as pragmatic deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies about pragmatic deficit have been reported by some scholars [2], [4], [6]. [4] attempts to explore the students' pragmatic deficit in bilingual family.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation